Peran Kredibilitas Influencer, Iklan, Citra Merek dalam Memengaruhi Keputusan Pembelian Produk Skincare di TikTok Shop - Kamila, Vera Rindiani; Hariyadi, Guruh Taufan; Nuryanto, Imam; Putra, Febrianur Ibnu Fitroh Sukono (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of Influencer Credibility, Advertising, and Brand Image on Purchasing Decisions for skincare products on TikTok Shop. A quantitative approach was used with a survey method of 139 respondents who are TikTok Shop users and have purchased skincare products. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS software. The results of the analysis show that Influencer Credibility and Brand Image have a positive and significant influence on Purchasing Decisions. Conversely, Advertising does not have a significant influence on Purchasing Decisions. These findings indicate that trust in influencers and positive perceptions of brands have a more dominant role in driving purchasing decisions than advertising. This study provides implications for business actors to optimize digital marketing strategies by emphasizing influencer credibility and strengthening brand image.